Pemanfaatan Sistem Informasi Bencana Banjir di Kabupaten Bandung Untuk Mewujudkan Masyarakat Tangguh Bencana - Dewi Wahyuni; Syamsunasir Syamsunasir; Adi Subiyanto; Mir’atul Azizah (PendIPA Journal of Science Education, 2022)
Bandung Regency often experiences flooding and the number of Early Warning System (EWS) equipment is still not sufficient. One of the targets of the Sendai Framework is to increase the coverage and access to the EWS until 2030. To prevent natural disasters and determine the efforts that must be made during a disaster to post-disaster, a disaster information system is needed. The purpose of the study was to determine the implementation of a flood disaster information system as an effort to reduce disaster risk and to determine the use of a flood disaster information system to create a disaster-resilient society. This research was a qualitative research with an exploratory research design. The research was conducted in May 2021 – January 2022 in Bandung Regency. Data collection techniques used were interviews, documentation, and observation, with analytical techniques using the Miles and Huberman model. There was no specific flood disaster information system however the information collected and processed by the Pusdalops was used as the basis for the preparation of a disaster risk reduction plan in Bandung Regency. Information on the potential for flooding was conveyed by the Pusdalops to the community so that people were alert and evacuate if it is not possible to stay at home. Community resilience, especially in three flood-prone villages, was in the primary category. A disaster information system is needed to support disaster risk reduction efforts and create a disaster-resilient society.